2020
DOI: 10.3390/nu12113343
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Early Introduction of Sugar Sweetened Beverages among Infants: Findings from the HSHK Birth Cohort Study

Abstract: Understanding the determinants of early introduction of sugar sweetened beverages (SSBs) may assist in designing effective public health interventions to prevent childhood weight related conditions (obesity). This study explores the relationship between family/infant characteristics and the early introduction of SSBs among infants in Sydney, Australia. Mothers (n = 934) from an ongoing birth cohort study were interviewed at 8, 17, 34, and 52 weeks postpartum. Multivariable logistic regression analysis was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…Poor diet, comprising of energy-dense, low-nutritious foods, and an earlier introduction of such foods can contribute to the rising prevalence of childhood obesity and ECC [ 11 , 12 ]. For example, earlier research from the Healthy Smiles Healthy Kids (HSHK) study [ 13 , 14 , 15 ] identified that 95% of infants were introduced to discretionary foods, and more specifically, almost 43% of infants were introduced to sugar beverages (SSBs) before the recommended age of 52 weeks [ 16 ]. The research team further noted that over 13% and over 76% of Sydney infants were introduced to solid foods before 17- and 26-weeks post-partum, respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poor diet, comprising of energy-dense, low-nutritious foods, and an earlier introduction of such foods can contribute to the rising prevalence of childhood obesity and ECC [ 11 , 12 ]. For example, earlier research from the Healthy Smiles Healthy Kids (HSHK) study [ 13 , 14 , 15 ] identified that 95% of infants were introduced to discretionary foods, and more specifically, almost 43% of infants were introduced to sugar beverages (SSBs) before the recommended age of 52 weeks [ 16 ]. The research team further noted that over 13% and over 76% of Sydney infants were introduced to solid foods before 17- and 26-weeks post-partum, respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these Australia-wide studies reported primary caregivers had a better knowledge about the effects of SSB on their children’s teeth [ 37 ], they also demonstrated that the diets of South Australian children aged 0– years contained free sugars in excess of WHO recommendations [ 26 ] and contrary to the Australian Dietary Guidelines recommendation that SSB should not be provided to children younger than 12 months [ 44 ]. This finding has been echoed in a New South Wales study on child obesity, which found 42.7% of its participant mothers reported they introduced SSB in their child’s diet before the age of 12 months [ 45 ]. Nutrition plays a significant role as the dietary experiences of a child in the first 1000 days of life have a profound impact on eating behaviours and food choices throughout life [ 46 ], thus healthy food promotion strategies need to incorporate messages about oral health appropriate foods and drinks [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although these Australia-wide studies reported primary caregivers had a better knowledge about the effects of SSB on their children's teeth (Stormon et al, 2019), they also demonstrated that the diets of South Australian children aged 0 to 2 years contained free sugars in excess of WHO recommendations (Devenish et al, 2019) and contrary to the Australian Dietary Guidelines recommendation that SSB should not be provided to children younger than 12 months (NHMRC, 2012). This nding has been echoed in a New South Wales study on child obesity, which found 42.7% of its participant mothers reported they introduced SSB in their child's diet before the age of 12 months (Irvine et al, 2020). Nutrition plays a signi cant role as the dietary experiences of a child in the rst 1000 days of life have a profound impact on eating behaviours and food choices throughout life (Moore et al, 2017), thus healthy food promotion strategies need to incorporate messages about oral health appropriate foods and drinks (Birch & Doub, 2014).…”
Section: The Oral Health Literacy Of Primary Caregivers In Australiamentioning
confidence: 95%